Green Stormwater Infrastructure Planning in Urban Landscapes: Understanding Context, Appearance, Meaning, and Perception - Mahbubur Meenar; Jordan P. Howell; Devon Moulton; Shane Walsh (Land, 2020)
Prior research has documented environmental and economic benefits of green stormwater infrastructure (GSI); literature on GSI social benefits is also becoming more prevalent among scholars around the world. This paper aims to understand whether GSI projects are considered as assets to urban neighborhoods or as projects that might introduce a new set of social concerns. Based on field observations of 238 GSI projects and 50 intercept interviews, we investigate selected social aspects of GSI, such as project context, visual appearance, recreational appeal, meaning, and public perception, in two neighboring US cities—Philadelphia and Camden. Analysis of field data and observation notes revealed that GSI project setting impacted recreational appeal; their appearance was related to maintenance and signage; and their interaction with the public depended on location, land use, and visual/recreational appeal. Most GSI sites with the presence of trash, but the absence of signage were found in potentially disadvantaged areas. According to intercept interviews, many people were not aware of GSI presence in the neighborhood, were not familiar with GSI or its functionality, did not find a way to get access to GSI or interact with them, and were generally concerned about poor design, defective construction, or lack of maintenance. We argue that lack of information and community care/support for GSI can result in social disinvestments in these projects, which can facilitate improper use and maintenance issues, affecting their intended basic environmental functions. Consistent with prior research, we speak to the importance of participatory planning processes in improving community acceptance and interests around GSI planning and installation in urban landscapes.